(untitled) (Eurasian Journal of Engineering and Technology, 2025)
This methodological guide provides recommendations and instructional guidelines for the effective and purposeful conduct of laboratory classes in the subject "Theory of Machines and Mechanisms." During the classes, students develop skills in understanding the principles of motion of mechanisms, analyzing them, and designing mechanical systems. The methodology outlines the stages of laboratory work, necessary equipment, methods of calculation and analysis, as well as the procedure for evaluating obtained results. Additionally, assignments and practical examples aimed at enhancing students’ independent working abilities are included. This guide is intended for students, instructors, and young specialists of higher technical educational institutions